Inovasi Produk Halal Pada Islamic Microfianance Institutions Dalam Mendukung Inklusi Keuangan Untuk Memenuhi Kebutuhan UMKM dan Milenial - Eny Latifah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2019)
The purpose of this study was to find out what innovation products existed in Non-Bank Islamic Financial Services Institutions in the Sunan Drajat Lamongan Islamic Boarding School Cooperative in supporting financial inclusion to meet the needs of MSMEs and Millennials. The results of this study are the Sunan Drajat Islamic Boarding School Cooperative having innovative halal products in the form of cash waqf savings, walimah savings, pregnant mother savings, santripreneur savings, education savings, umrah savings, rihlah savings, mudharabah savings, sholeh children savings, old age savings fulfill millennial and MSME needs to support financial inclusion. The above products are able to meet the needs of millennials and MSMEs with various facilities they have as a form of encouragement in increasing financial inclusion.